Genetic diversity of Colletotrichum gloeosporioides in Nigeria using amplified fragment length polymorphismA (AFLP) markers - Aduramigba-Modupe, A.O.; Asiedu, Robert; Odebode, C.A.; Owolade, F. (Academic Journals, 2012)
Colletotrichum gloeosporioides is the causal agent of yam anthracnose disease in Nigeria. Differential cultivars and amplified fragment length polymorphic DNA markers were used to assess the extent of genetic diversity among 39 isolates of the pathogen. Fourteen (14) pathotypes of the pathogen were identified based on inoculation of a differential set of Dioscorea alata genotypes of which pathotype P11 was the most virulent attacking all differential D. alata host genotypes, while pathotype P8 was the least virulent. 52% of the isolates were avirulent, 23% were slightly virulent and 25% were virulent. Amplified fragment length polymorphism (AFLP) analysis confirmed genetic variation among the C. gloeosporioides isolates and was effective in establishing genetic relationships between them. However, the grouping of the isolates based on AFLP analysis was not directly related to virulence groups or geographical origin of the isolates. The genetic variation in C. gloeosporioides is important in choosing strategies to develop durable resistance